Evaluasi Pengalaman Pengguna Menggunakan Usability Testing dan User Experience Questionnaire (UEQ) (Studi pada E-Commerce Fashion) - Sonia Elisurya; Hanifah Muslimah Az-Zahra; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Internet has become a part of society's daily routine. One of the activities carried out through the internet is online transactions. Following the growth of online transactions also makes the emergence of various types of e-commerce to meet people's needs. Fashion e-commerce is one of many e-commerce type that often used to fulfill people's need. E-Commerce XYZ, Vipplaza.co.id and Berrybenka are fashion e-commerce engaged in the same field and have common characteristics. This study aims to compare the user experience gained while using all three e-commerce websites that have the same characteristics and business processes. This research was carried out using the scenario testing method and User Experience Questionnaire (UEQ). The scenario testing will be carried out for 10 new users based on four parameter: task completed, error rate, number of clicks and time per completed task. User Experience Questionnaire (UEQ) has 6 measurement scales and will be filled by 25 respondents. After testing section and fill the questionnaire, the respondent will be interviewed to find out the responses and problems during the scenario testing. The conclusion from the result shows that E-Commerce XYZ has a better level of user experience than Vipplaza.co.id and Berrybenka.com